2010
DOI: 10.1628/001522110x503370
|View full text |Cite
|
Sign up to set email alerts
|

Voting on Thresholds for Public Goods: Experimental Evidence

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…A common feature in all treatments as compared to Baseline is that participants actively choose one organization over the other. If such a choice induces self-commitment, we should observe an higher level of compliance for the selected organization as compared to the non-selected organization (Rauchdobler, Sausgruber, and Tyran, 2010). Since commitment is stronger when it is made publicly, a corollary of this hypothesis is that commitment should be stronger when the decision is made in group, and even stronger when the group decision happens after the ability to coordinate.…”
Section: Hypothesis 2 (Social Coordination) Thanks To the Opportunity To Coordinate Participants Inmentioning
confidence: 95%
“…A common feature in all treatments as compared to Baseline is that participants actively choose one organization over the other. If such a choice induces self-commitment, we should observe an higher level of compliance for the selected organization as compared to the non-selected organization (Rauchdobler, Sausgruber, and Tyran, 2010). Since commitment is stronger when it is made publicly, a corollary of this hypothesis is that commitment should be stronger when the decision is made in group, and even stronger when the group decision happens after the ability to coordinate.…”
Section: Hypothesis 2 (Social Coordination) Thanks To the Opportunity To Coordinate Participants Inmentioning
confidence: 95%
“…We give a brief overview of the relevant researches as follows. The existence of a threshold in TPGG is positive, in general, for cooperation given that free-riding is no longer the dominant strategy due to the existence of multiple equilibria and the amount of cooperation is aected by the level of the threshold [32][33][34][35]. Uncertainty about the threshold level of contributions needed for successful action is one factor that potentially aects individuals' decisions to participate in a collective action [36][37][38].…”
Section: Contentsmentioning
confidence: 99%
“…Rondeau and List (2008) found higher contributions for higher threshold levels in a fundraising field experiment, but the increase in contributions was insignificant. Rauchdobler, Sausgruber, and Tyran (2009) showed that imposing thresholds in public good games could also result in lower contribution rates.…”
Section: Preferences In Public Good Provision Under Conditions Of Povertymentioning
confidence: 99%